Comparison study of gut microbiota in case of Parkinson’s disease and other neurological disorders - V. A. Petrov; V. M. Alifirova; I. V. Saltykova; I. A. Zhukova; N. G. Zhukova; Yu. B. Dorofeeva; A. V. Tyakht; I. A. Altukhov; E. S. Kostryukova; M. A. Titova; Yu. S. Mironova; O. P. Izhboldina; et al. (Бюллетень сибирской медицины)
Currently the role of microbiota in diseases pathogenesis, its therapeutic and diagnostic potential are of the utmost interest for scientists and medical doctors. Parkinson’s disease is neurodegenerative disorder for which microbiota’s dysbiosis was previously shown.The main goal of the study is to compare the colon microbiota composition in case of Parkinson’s disease and other neurological pathologies, including idiopathic familial dystonia, essential tremor, multiple sclerosis, multiple system atrophy in order to determine the intestinal flora landscape specific to Parkinson’s disease.Material and methods. One hundred twenty-six patients, 93 with Parkinson’s disease and 33 with other neurological pathology were examined. For all patients, physical examination and fecal samples collection were performed. Microbiota taxonomic composition was analyzed by sequencing of bacterial 16S rRNA genes followed by bioinformatic and statistical analysis.As a result of the study, significant differences between groups in microbiota composition were found. Gut microbiota of patients with Parkinson’s disease was characterized by increase of Desulfovibrio piger, Lactobacillus mucosae, Yokenella regensburgei, Alistipes indistinctus, Oscillospira capillosus, Clostridium bolteae, Soleaferrea massiliensis, Butyricimonas virosa, Dorea massiliensis, Victivallis vadensis abundances. Patients with other neurological diseases had increased levels of bacteria belonging to Blautia, Intestinibacter, Coprococcus genera and Anoxystipes fissicatena, Fusobacterium periodonticum, Gemmiger formicilis, Papillibacter cinnamivorans, Roseburia faecis, Lachnoclostridium indolis, Clostridium populeti, Clostridium tertium, Roseburia intestinalis, Eubacterium desmolans, Eubacterium cylindroides, Clostridium clariflavum, Eubacterium eligens, Coprococcus eutactus, Intestinibacter bartlettii species in their gut microbiota.Consequently, gut microbiota in case of Parkinson’s disease was different from the microbiota of patients with other neurological diseases, including neuroinflammatory and neurodegenerative disorders, in terms of taxonomic diversity and composition.